2015
DOI: 10.1007/s10856-015-5626-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined delivery of PDGF-BB and BMP-6 for enhanced osteoblastic differentiation

Abstract: Natural microenvironment during bone tissue regeneration involves integration of multiple biological growth factors which regulate mitogenic activities and differentiation to induce bone repair. Among them platelet derived growth factor (PDGF-BB) and bone morphogenic protein-6 (BMP-6) are known to play a prominent role. The aim of this study was to investigate the benefits of combined delivery of PDGF-BB and BMP-6 on proliferation and osteoblastic differentiation of MC3T3-E1 preosteoblastic cells. PDGF-BB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Furthermore, PDGF induces osteoblast differentiation by enhancing collagen synthesis and bone cell proliferation as well as tissue repair [17,18]. Demirtas et al [19] reported that isolated PDGF induced two-fold proliferation of osteoblasts in comparison with the control in vitro. In the current study, both fresh-PRP and FD-PRP has similar effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PDGF induces osteoblast differentiation by enhancing collagen synthesis and bone cell proliferation as well as tissue repair [17,18]. Demirtas et al [19] reported that isolated PDGF induced two-fold proliferation of osteoblasts in comparison with the control in vitro. In the current study, both fresh-PRP and FD-PRP has similar effects.…”
Section: Discussionmentioning
confidence: 99%
“…SP-1 P recruits osteoblast precursors ( Meshcheryakova et al, 2017 ), promotes osteoblast proliferation, differentiation, activity, and survival ( Higashi et al, 2016 ; Meshcheryakova et al, 2017 ). BMP6 induces osteoblast differentiation ( Demirtaş et al, 2016 ) and bone mineralization ( Luo et al, 2011 ; Zhu et al, 2012 ). In addition to its role in bone resorption, TRAP acts as a clastokine by facilitating osteoblast proliferation and differentiation ( Gradin et al, 2012 ).…”
Section: Osteoclast Phenotype Functions and Biological Activitiesmentioning
confidence: 99%
“…Recently, radiopaque beads (ROB) have been developed for embolization. Unlike traditional embolic microparticles, ROBs have iodine bound within their structure, which allows for real-time visualization of spatial distribution under standard clinical imaging [3, 5, 7-9]. This information has the potential to better define procedural endpoints, predict localized drug delivery and provide a higher level of patient specific treatment [3, 4, 7, 8, 10].…”
Section: Introductionmentioning
confidence: 99%